The Grand Mosque of Buton Sultanate as the Place for Insan Kamil - Umar, Muhammad Zakaria; Radja, Abdul Mufti; Sir, Mohammad Mochsen; Harisah, Afifah (Journal of Islamic Architecture, 2025)
Buton Island, located in Southeast Sulawesi Province, Indonesia, was historically part of the Buton Sultanate, whose governance included Sara Kidhina (religious authority) within the Buton Palace Fortress. The Grand Mosque of the Sultanate of Buton (TGMOTSOB), established in 1541 during the reign of Sultan Murhum, served as the religious and customary center. Now over 480 years old and still active, TGMOTSOB has undergone structural and functional changes, raising concerns about the fading of its original design concept. This study examines TGMOTSOB through the local wisdom of Bhincibhinciki Kuli (BbK), a Butonese life philosophy meaning “before pinching another’s pain, first pinch your own,” which predates Islam and was later integrated with Islamic Sufism to form Islamic BbK. Using Husserl’s transcendental phenomenology, employing phenomenological and eidetic reduction data were collected through in-depth interviews and analyzed inductively with rational validation. The study concludes that the conceptual essence of TGMOTSOB reflects the Sufi notion of Insan Kamil.